(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Bankim Chandra Chattopadhyay’s novel ’Mrnalini’ is based on the attack of the Turkish invader Bakhtiyar Khilji on Lakshman Sen, the ruler of Nabadwip in Bengal. In which he highlights the weakness of old Lakshmana Sen and the intrigues of his courtiers. As a result, Bakhtiyar Khilji captured Lakhnauti with only Eighteenth cavalry. I am trying to verify the historical analysis of his novel in this essay. I have tried to explain in the light of history by quoting from the novel. All the names of the characters mentioned in the novel have no historical authenticity. However, despite statistical errors, several similarities are found with the events. My main point here is that there was a big conspiracy behind the defeat of Laxman Sen, the ruler of Lakhnauti. Because it was not possible for Bakhtiyar to defeat the then powerful king Lakshmana Sen of the Sena dynasty with only eighteenth Cavalry. This royal conspiracy is also described quite a bit in the novel. I have discussed this in my article. So anyway, a novel based on history needs a bit of imagination to make it more interesting. But it is our duty to analyze it in a historical light.